Managing Projects with PMBOK 7 : Connecting New Principles with Old Standards - Marion, James (Business Expert Press, 2022)
The guide to the project management body of knowledge (PMBOK) published by the Project Management Institute provides a roadmap of performance domains designed to support project managers in all phases of project management. The sheer number of models, methods, and arti-facts may leave project managers in a quandary about where to start and how to apply the many components. This book provides a simple explanatory guide for the layman that clarifies the "big picture" of the PMBOK.